High Patient Satisfaction with Deep Sedation for Catheter Ablation of Cardiac Arrhythmia. Issue 5 (25th April 2017) - MÜNKLER, PAULA; ATTANASIO, PHILIPP; PARWANI, ABDUL SHOKOR; HUEMER, MARTIN; BOLDT, LEIF‐HENDRIK; HAVERKAMP, WILHELM; WUTZLER, ALEXANDER
Abstract : Background: Patients' satisfaction with invasive procedures largely relies on periprocedural perception of pain and discomfort. The necessity for intraprocedural sedation during catheter ablation of cardiac arrhythmias for technical reasons is widely accepted, but data on patients' experience of pain and satisfaction with the procedural sedation are scarce. We have assessed patients' pain and discomfort during and after the procedure using a standardized questionnaire. Methods: One hundred seventeen patients who underwent catheter ablation answered a standardized questionnaire on periprocedural perception of pain and discomfort after different anesthetic protocols with propofol/midazolam with and without additional piritramide and ketamine/midazolam. Results: Patients report a high level of satisfaction with periprocedural sedation with 83% judging sedation as good or very good. The majority of patients was unconscious of the whole procedure and did not recollect experiencing pain. Procedural pain was reported by 7.7% of the patients and 16% reported adverse effects, e.g., postprocedural nausea and episodes of headache. Conclusion: The results of our study show that deep sedation during catheter ablation of cardiac arrhythmias is generally well tolerated and patients are satisfied with the procedure. Yet, a number of patients reports pain or adverse events. Therefore, studies comparing different sedation strategies should be conducted in order to optimize sedation and analgesia.